TOKOH WANITA DAN NILAI MORAL DALAM NOVEL DISGUISED (SANG PENYAMAR): MEMOAR MASA PERANG KARYA RITA LA FONTAINE DE CLERCQ ZUBLI - Asropah, Asropah; Listyarini, Ikha (SASINDO, 2013)
Prominent Women and Moral Value in Disguised Novel (TheDisillusionment): Wartime Memoirs of work Rita La Fontaine De Clercq Zubli